Nexus of stakeholder integration, green investment, green technology adoption and environmental sustainability practices: evidence from Bangladesh textile SMEs - Hossain, Mohammad Imtiaz; Tze, San Ong; Teh, Boon Heng; Mohd Said, Ridzwana; Siow, May Ling (Universiti Putra Malaysia Press, 2022)
This study investigates the sway of stakeholder integration and green investment on Environmental Sustainability Practices (ESP), as well as the moderating role of Green Technology Adoption (GTA) in Bangladesh Textile small and medium enterprises (SMEs). A questionnaire has been used to collect data from 140 textile SMEs and analysed using the quantitative survey method. The findings have revealed that Buyer Pressure (BP), Governmental regulations (GR), and Green Investment (GI) have significant effects on ESP, but not Supplier pressure (SP). The study has also evidenced the insignificant moderating influence of GTA on the relationships among BP, GR, GI, except SP. This study makes a conceptual contribution by highlighting the relationships among these constructs and confirming the lack of stakeholder integration. The findings of the research extend the understanding and comprehensiveness of Stakeholder theory (ST) and Transaction Cost Economics (TCE) theory by providing empirical insights from the firm level. Consequently, the outcomes promote environmental practices and offer food for thought for policymakers, compliance managers, entrepreneurs, and relevant stakeholders.